Soluble CD40 ligand release in patients with stable coronary artery disease during elective stent implantation: Effect of drug-eluting stent over bare metal stent - TİGEN, MUSTAFA KÜRŞAT (Turkish Anaesthesiology and Intensive Care Society, 2013)
Objectives: We aimed to determine the effect of drug-eluting stent (DES) implantation on soluble CD40 ligand (sCD40L) levels in patients with stable coronary artery disease undergoing stent replacement. Study design: Eighty-nine consecutive patients (33 women, 56 men; mean age 61±10 years) with stable coronary artery disease undergoing stent replacement were recruited. Pre- and post-procedural blood samples were collected for sCD40L analysis, and differences in plasma levels were calculated and expressed as delta sCD40L. Total size and length of implanted stents and pre- and post-dilatation procedures were recorded for each patient, for possible impact on sCD40L release. Patients were followed for one year following procedures for possible adverse cardiac events such as death, myocardial infarction and revascularization. Results: Forty-nine patients received bare metal stent (BMS) and 40 patients received DES. There were no differences between BMS- and DES-implanted patients in terms of age, stent size and length, and delta sCD40L plasma levels. Delta sCD40L was correlated only with total implanted stent length (r=0.374, p<0.001). Delta sCD40L levels were divided into quartiles for better determination of the procedural parameters that are effective on biomarker release. Total stent length (p=0.008), stent size (p=0.038) and pre-dilatation procedure (p=0.034) were the statistically differing parameters between delta sCD40L quartiles. Although statistically non-significant, all three adverse events were observed in patients with the highest quartile (p=0.179). Conclusion: Procedural sCD40L release did not differ between DES- and BMS-implanted stable coronary artery disease patients. Total implanted stent length, stent size and pre-dilatation procedure were the influential parameters on procedural sCD40L release. © 2013 Turkish Society of Cardiology.
Keywords: Angioplasty, transluminal, percutaneous coronary; Biological markers/blood; Cd40 ligand/blood; Coronary artery disease/ blood; Drug-eluting stents; Platelet aggregation inhibitors; Stents